A Review of the Various Roles and Participation Levels of B-Cells in Non-Infectious Uveitis - Zhu, Lei; Chen, Binyao; Su, Wenru (Frontiers in Immunology, 2021)
Non-infectious uveitis is an inflammatory disorder of the eye that accounts for severe visual loss without evident infectious agents. While T cells are supposed to dominate the induction of inflammation in non-infectious uveitis, the role of B cells in the pathogenesis of this disease is obscure. Therefore, this review aimed to discuss diverse B-cell participation in different non-infectious uveitides and their roles in the pathogenesis of this disease as well as the mechanism of action of rituximab. Increasing evidence from experimental models and human non-infectious uveitis has suggested the participation of B cells in non-infectious uveitis. The participation levels vary in different uveitides. Furthermore, B cells play multiple roles in the pathogenic mechanisms. B cells produce autoantibodies, regulate T cell responses via antibody-independent functions, and constitute ectopic lymphoid structures. Regulatory B cells perform pivotal anti-inflammatory functions in non-infectious uveitis. Rituximab may work by depleting pro-inflammatory B cells and restoring the quantity and function of regulatory B cells in this disease. Identifying the levels of B-cell participation and the associated roles is beneficial for optimizing therapy. Diversified experimental model choices and emerging tools and/or methods are conducive for future studies on this topic.